2015
DOI: 10.1111/birt.12176
|View full text |Cite
|
Sign up to set email alerts
|

Seeing and Holding Baby: Systematic Review of Clinical Management and Parental Outcomes After Stillbirth

Abstract: BackgroundIn 2009 there were an estimated 2.6 million stillbirths worldwide. In the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 51 publications
(231 reference statements)
5
39
1
Order By: Relevance
“…The findings of this review suggest that the manner in which health care professionals approach and provide care for parents experiencing stillbirth may be remembered by parents well into the future and may have a lasting impact on parents' grief and subsequent well being. This is in agreement with previous research and highlights the importance of clear evidence‐based guidance for health care professionals and health services about care during and after stillbirth to achieve the best possible outcomes for parents and other family members. The findings of this review have, with consultation from an expert advisory group, informed the creation of evidence‐based guidance for health care professionals on the provision of meaningful care strategies for parents who experience stillbirth .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings of this review suggest that the manner in which health care professionals approach and provide care for parents experiencing stillbirth may be remembered by parents well into the future and may have a lasting impact on parents' grief and subsequent well being. This is in agreement with previous research and highlights the importance of clear evidence‐based guidance for health care professionals and health services about care during and after stillbirth to achieve the best possible outcomes for parents and other family members. The findings of this review have, with consultation from an expert advisory group, informed the creation of evidence‐based guidance for health care professionals on the provision of meaningful care strategies for parents who experience stillbirth .…”
Section: Discussionsupporting
confidence: 92%
“…Parents who had not seen their baby often expressed regret at not having done so or not having done more with their babies . This result concurs with the findings of a recent review that focused on evidence of benefit and harm for parents after seeing and holding their stillborn baby, and concluded that contact with the baby may be beneficial for parents' well being after stillbirth . The findings of this review suggest that the manner in which health care professionals approach and provide care for parents experiencing stillbirth may be remembered by parents well into the future and may have a lasting impact on parents' grief and subsequent well being.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Client centred communication is an important aspect of the midwifepatient relationship and women appreciated continuity of care that followed individualized pathways (Baas, Erwich, Wiegers, de Cock, & Hutton, 2015). Similar findings from a qualitative synthesis were recommended for those parents who had experienced intrauterine death and stillbirth (Lisy, Peters, Riitano Jordan, & Aromataris 2016; see also Kingdom, Givens & O'Donnell, 2015).…”
Section: Making Things Better: Continuity Of Care and Feeling In Controlmentioning
confidence: 85%
“…According to others, however, seeing, touching the child and saying goodbye are associated with lower levels of anxiety and depression for the two years following death (Cacciatore et al, 2008;Kingdon et al, 2015;Reynolds, 2004;Wijngaards-de Meij et al, 2008). Having known the real child and being in contact with him can therefore mitigate the levels of grief, providing a comfort and comparison in the process of recognition and acceptance of death (Wijngaardsde Meij et al, 2008).…”
Section: Summary Frequencymentioning
confidence: 98%